Cysteine and Aspartyl Proteases Contribute to Protein Digestion in the Gut of Freshwater Planaria. - Louise S Goupil; Sam L Ivry; Ivy Hsieh; Brian M Suzuki; Charles S Craik; Anthony J O'Donoghue; James H McKerrow (Public Library of Science (PLoS), 2016)
Proteases perform numerous vital functions in flatworms, many of which are likely to be conserved throughout the phylum Platyhelminthes. Within this phylum are several parasitic worms that are often poorly characterized due to their complex life-cycles and lack of responsiveness to genetic manipulation. The flatworm Schmidtea mediterranea, or planaria, is an ideal model organism to study the complex role of protein digestion due to its simple life cycle and amenability to techniques like RNA interference (RNAi). In this study, we were interested in deconvoluting the digestive protease system that exists in the planarian gut. To do this, we developed an alcohol-induced regurgitation technique to enrich for the gut enzymes in S. mediterranea. Using a panel of fluorescent substrates, we show that this treatment produces a sharp increase in proteolytic activity. These enzymes have broad yet diverse substrate specificity profiles. Proteomic analysis of the gut contents revealed the presence of cysteine and metallo-proteases. However, treatment with class-specific inhibitors showed that aspartyl and cysteine proteases are responsible for the majority of protein digestion. Specific RNAi knockdown of the cathepsin B-like cysteine protease (SmedCB) reduced protein degradation in vivo. Immunohistochemistry and whole-mount in situ hybridization (WISH) confirmed that the full-length and active forms of SmedCB are found in secretory cells surrounding the planaria intestinal lumen. Finally, we show that the knockdown of SmedCB reduces the speed of tissue regeneration. Defining the roles of proteases in planaria can provide insight to functions of conserved proteases in parasitic flatworms, potentially uncovering drug targets in parasites.